A novel semi‐dry method for the simultaneous removal of Hg and SO2 using spray drying absorption method. Issue 5 (24th February 2020) - Yi, Honghong; Du, Chengcheng; Ma, Yueqiang; Tang, Xiaolong; Zhao, Shunzheng; Gao, Fengyu; Yang, Zhongyu; Huang, Yonghai; Yang, Kun; Xie, Xizhou
Abstract: BACKGROUND: A novel semi‐dry method called SDA (spray drying absorption) for the simultaneous removal of mercury (Hg 0 ) and sulfur dioxide (SO2 ) have been proposed in this article, in which Hg 0 was initially oxidized by gaseous oxidant (O3 ) and liquid oxidant (K2 S2 O8, H2 O2, and NaClO2 ), after which SO2 and Hg 2+ were absorbed by Ca(OH)2 . RESULTS: The effects on different process conditions and additives on Hg 0 removal were explored at first, and the results indicated that the Hg removal efficiency could be improved by oxidizing or extending the residence time of the liquid phase reaction. When SO2 and Hg coexist in the atmosphere, additives including oxidants or composite additives were added into the mixed system, and the results indicated that the best removal efficiency of SO2 and Hg was about 99.5% and 51% respectively. CONCLUSION: Since SO2 has good water solubility, it would affect the oxidation of Hg and the removal of Hg. When there was nitric oxide (NO) in the atmosphere, a new stable product was generated which contributed to the removal of Hg, and the removal efficiency of SO2 and Hg was about 99.5% and 57% respectively. © 2020 Society of Chemical Industry